1998
DOI: 10.1007/s004210050371
|View full text |Cite
|
Sign up to set email alerts
|

Summation of elementary phonomyograms during isometric twitches in humans

Abstract: To study its summation principle, the phonomyogram (PMG) from the first interosseus dorsalis muscle was recorded in five subjects during single twitches evoked by electrical stimulation over the motor point. By increasing the current pulse from threshold to maximal intensity, PMG amplitude increased linearly with motor unit recruitment. The twitch amplitude-intensity relationship was also linear. The PMG amplitude was therefore linearly related to the external force. For all these relationships highly signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 32 publications
1
37
0
Order By: Relevance
“…The amplitude of the MMG increases with the number of recruited MUs, whereas it decreases with higher firing rate due to fusion of the MU mechanical activity (Bichler 2000;Orizio et al 1993;Petitjean et al 1998;Stokes and Cooper 1992). The MMG-amplitude/force relationship may be broadly divided into two contiguous force regions, in which recruitment is the major mechanism for force production, and rate coding plays the prominent role (Akataki et al 1999;Matheson et al 1997;Orizio et al 1989).…”
Section: Amplitude Characteristicsmentioning
confidence: 96%
“…The amplitude of the MMG increases with the number of recruited MUs, whereas it decreases with higher firing rate due to fusion of the MU mechanical activity (Bichler 2000;Orizio et al 1993;Petitjean et al 1998;Stokes and Cooper 1992). The MMG-amplitude/force relationship may be broadly divided into two contiguous force regions, in which recruitment is the major mechanism for force production, and rate coding plays the prominent role (Akataki et al 1999;Matheson et al 1997;Orizio et al 1989).…”
Section: Amplitude Characteristicsmentioning
confidence: 96%
“…The authors suggested that the MMG recorded from a contracting muscle re¯ects the summation of elementary MMG signals that occur during voluntary contractions. Moreover, a connection between the increase in MMG amplitude and motor unit recruitment process was observed by Petitjean et al (1998) during evoked contractions of the human ®rst dorsal interosseus muscle. Orizio et al (1993) drew similar conclusions to those of Petitjean et al (1998) in an earlier study of contractions of the cat gastrocnemius muscle.…”
Section: Introductionmentioning
confidence: 92%
“…Moreover, a connection between the increase in MMG amplitude and motor unit recruitment process was observed by Petitjean et al (1998) during evoked contractions of the human ®rst dorsal interosseus muscle. Orizio et al (1993) drew similar conclusions to those of Petitjean et al (1998) in an earlier study of contractions of the cat gastrocnemius muscle. It was therefore generally supposed that each activity of a single motor unit generates a MMG signal.…”
Section: Introductionmentioning
confidence: 92%
“…The subsequent component, t EMG-MMG, includes events that are mainly electrochemical in nature, spanning from the propagation of the motor unit action potential at the sarcolemmal level to myosin head rotation, together with the pressure wave transmission to the skin surface detected by MMG (Hufschmidt 1985;Petitjean et al 1998). The longer t EMG-MMG in DM1 may be explained by the alteration in the splicing of several proteins, such as SERCA1 and CACNA1S, involved in Ca 2+ homeostasis and in excitation-contraction coupling mechanism [6][7][8][9][10] thus possibly leading to a lengthened duration of the dihydropyridine and ryanodine receptors interaction, Ca 2+ release by sarcoplasmic reticulum, and troponin activation [9,10,35].…”
Section: Delays During Muscle Contractionmentioning
confidence: 99%
“…When also MMG is recorded, the three signals allow the partitioning of the total electromechanical delay (Delay TOT ) into (i) a mainly electrochemical component, which includes the events from the propagation of the motor unit action potential at the sarcolemmal level to myosin head rotation and pressure wave transmission to the skin surface [28,29], and (ii) a mainly mechanical component, which reasonably provides a potential index of the time required for taking up the muscle-tendon unit slack, before F transmission becomes efficient at the tendon insertion point [12][13][14]16]. When the muscle is electrically activated, the simultaneous recording also of the stimulation current (Stim) offers an additional Delay TOT component between Stim and EMG onset, related to the presynaptic and synaptic events [16].…”
Section: Introductionmentioning
confidence: 99%